Difficult Component Areas of Research Experienced by Lecturers in the Faculty of Education, Federal University of Kashere, Gombe State. - Onipede, O.; Lawal, O. I.; Kunta, D. (Kashere Journal of Education, 2021)
The study was conducted to ascertain difficult component areas of research experienced by lecturers in the faculty of Education, Federal University of Kashere. Three (3) purposes and three (3) research questions guided the study. The population of the study was 155 lecturers in the faculty. Purposive sampling techniques was used to select a sample of 65 lecturers below the rank of Associate Professor who were not on study fellowship. A 31 items questionnaire developed from literature reviewed was use to collect data for the study. Data collected for the study was analyzed using mean, standard deviation and Need-gap analysis to answer the research questions while t test statistic was used to test the null hypothesis at 0.05 level of significance. It was found out that lecturers in the Faculty of Education, Federal University of Kashere experienced difficulties is some aspect of research such as conceptualizing research problem, writing the background of the study relating all variables of the study, conceptual and theoretical framework, research methods, interpretation of results among others. It was recommended that the Dean Faculty of Education should organize seminar and workshop for the lecturers on principles of conducting and writing research.